PENGARUH PENGGUNAAN MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS VI DI SD NEGERI GAROT KABUPATEN ACEH BESAR - Fajar Nabila, Putri; Fitri, Aida; Hasniyati, Hasniyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The short story writing skills of sixth-grade students at SD Negeri Garot still need improvement, particularly in composing coherent plot sequences and developing ideas systematically. This study aims to determine the effect of using the Picture and Picture model on the short story writing skills of sixth-grade students at SD Negeri Garot, Aceh Besar Regency. A quantitative approach with quasi-experimental design (Nonequivalent Control Group Design) was employed. The population consisted of 48 sixth-grade students. The sample comprised two classes: VI A as the control class (24 students) and VI B as the experimental class (24 students). Data collection was conducted through short story writing tests (pretest and posttest). Data analysis used SPSS version 26, including normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. Results showed the experimental class pretest mean of 69.71 increased to 80.17 in the posttest, while the control class increased from 65.75 to 74.42. The independent sample t-test showed a significance value of 0.011 (p < 0.05), thus H₀ was rejected and Hₐ was accepted. Therefore, there is a significant effect of using the Picture and Picture model on short story writing skills of sixth-grade students at SD Negeri Garot, Aceh Besar Regency.